Firm structure and corporate cash holdings - Subramaniam, Venkat; Tang, Tony T.; Yue, Heng; Zhou, Xin (Journal of Corporate Finance, 2011)
We analyze whether the organizational structure of firms (i.e., whether a firm is diversified or focused) affects their cash holdings. Using Compustat firm level and segment-level data, we find that diversified firms hold significantly less cash than their focused counterparts. Our results are robust to industry adjustments at the segment level and to different factors previously found to be important determinants of cash holdings. Using time-series, cross-sectional, and additional robustness tests we are able to attribute the lower cash holdings among diversified firms to complementary growth opportunities across the different segments of these firms and the availability of active internal capital markets. We find that the other theories that rely on the potentially effective use of asset sales of non-core segments of diversified firms to generate cash, and the increased agency/influence costs in diversified firms do not offer an economically significant explanation for the lower cash holdings among diversified firms.